Conformation of DNA in chromatin core particles containing poly(dAdT)-poly(dAdT) studied by 31 P NMR spectroscopy. - Simpson, R T (1979)
We have prepared semi-synthetic chromatin core particles from a complex of chicken erythrocyte inner histones (H2A, H2B, H3 and H4) with double-stranded poly(dAdT).poly(dAdT) and studied the conformation of the phosphodiester backbone using 31P NMR at 109.3 MHz. At 20 degrees C, the core particle spectrum is fit well by a single Lorenzian distribution with a line width of 110 Hz. This signal is significantly broader than that for the 145 base pair poly(dAdT).poly(dAdT) alone; the latter consists of two resonances, approximately equal in intensity, with average line width 41 Hz. Major changes in the spectrum ensue on heating the core particle preparation. In conjunction with other results (1) these data suggest four states for the core particle at increasing temperatures. Additionally, analysis of the spectrum of the unmelted core particle and its differences from protein-free DNA of the same length suggests that the conformation of the phosphodiester backbone and/or its interactions with histones along the length of the core particle DNA segment may not be uniform.